Cell envelope maintenance by PhoP is essential for Mycobacterium tuberculosis methylglyoxal resistance - Phuong M. Tran; Andrea Anaya-Sanchez; Daisy X. Ji; Madeline C. R. Schwarz; Shiva K. Angala; Mary C. Jackson; Sarah A. Stanley; K. Heran Darwin (Proceedings of the National Academy of Sciences, 2025)
During Mycobacterium tuberculosis infections bacteria are engulfed by macrophages, a main line of defense against invading pathogens. Upon activation, macrophages increase glycolysis, producing the antibacterial aldehyde methylglyoxal. To test whether bacterial methylglyoxal resistance is required for robust infections, we sought to identify M. tuberculosis defense mechanisms against methylglyoxal. We identified phoP mutants were among the most highly sensitive strains to methylglyoxal in vitro. phoP mutants are highly attenuated in mice but a phoP mutant was even more attenuated in mice that accumulate methylglyoxal. We further found phoP bacilli were more permeable to methylglyoxal and accumulated glycated proteins. Suppressor mutations in the fatty acid β-oxidation genes fadE25 or fixB restored impermeability and resistance to methylglyoxal to a phoP mutant. Together, our data show that an important role for PhoP is to provide M. tuberculosis resistance to methylglyoxal toxicity in vivo by regulating cell envelope integrity.